Pengaruh Lingkungan Kerja dan Work-Life Balance Terhadap Retensi Karyawan Melalui Kepuasan Kerja Sebagai Mediator Pada Generasi Z - Rio Alfian Rosid; Osly Usman (Indonesian Democracy Research Center, 2026)
The high turnover of Generation Z workers has become a structural problem for technology startups in Indonesia rather than a temporary operational disruption. Having grown up within a digital ecosystem, this generation displays a distinct work orientation in which loyalty is no longer extended to institutions but to work experiences perceived as meaningful. This study examines how the work environment and work-life balance affect employee retention, both directly and through job satisfaction as an intervening mechanism. A quantitative explanatory approach was employed using primary data from 150 Generation Z employees in the startup technology sector, collected through a five-point Likert questionnaire. The analysis used Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4, while the scholarly positioning was traced through a bibliometric analysis using VOSviewer. The examination of seven hypotheses confirmed that all were supported. Work environment and work-life balance positively and significantly affected both job satisfaction and retention, and job satisfaction partially mediated both relationships. These findings revise the long-held assumption that retention is solely a matter of compensation; for Generation Z, the quality of work relationships and respect for the boundaries of personal life are equally, if not more, decisive in the decision to stay.